1999
DOI: 10.1002/(sici)1096-9845(199911)28:11<1219::aid-eqe861>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Seismic effectiveness of tuned mass dampers considering soil-structure interaction

Abstract: SUMMARYThis paper presents how soil}structure interaction a!ects the seismic performance of Tuned Mass Dampers (TMD) when installed on #exibly based structures. Previous studies on this subject have led to inconsistent conclusions since the soil and structure models employed considerably di!er from each other. A generic frequency-independent model is used in this paper to represent a general soil}structure system, whose parameters cover a wide spectrum of soil and structural characteristics. The model structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…However, the design of TMDs is generally carried out based on the rigid‐base assumption—see, for example, Salvi and Rizzi 3 presented a tuning procedure based on the minimax algorithm for tuning the free TMD parameters for seismic applications. It is well recognized that dynamics characteristics—for example, fundamental frequencies, shape modes, and damping ratios—are altered due to soil–structure interaction (SSI) effects, especially on soft soil 4,5 . Therefore, it is imperative to investigate SSI effects on the effectiveness of TMD devices for multistory structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the design of TMDs is generally carried out based on the rigid‐base assumption—see, for example, Salvi and Rizzi 3 presented a tuning procedure based on the minimax algorithm for tuning the free TMD parameters for seismic applications. It is well recognized that dynamics characteristics—for example, fundamental frequencies, shape modes, and damping ratios—are altered due to soil–structure interaction (SSI) effects, especially on soft soil 4,5 . Therefore, it is imperative to investigate SSI effects on the effectiveness of TMD devices for multistory structures.…”
Section: Introductionmentioning
confidence: 99%
“…The performance and effectiveness of a TMD device are reduced as the period of the TMD deviates away from the natural period of the structure. Wu et al concluded that when soil is very soft, TMD cannot effectively reduce the seismic response of the soil‐structure system. On the other hand, when soil is moderately stiff, TMD should be tuned to the natural period of the soil‐structure system instead of the fixed‐based structure, in order to optimize the seismic performance of TMD.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al (1996) analyze the TMD behavior when facing seismic excitations and conclude that they are as efficient in the control of a soil-structure system as in the fixed base structures, as long as the soil-structure fundamental frequency is accurately estimated for the damper tuning. Wu et al (1999) studied how the SSI affects the TMD seismic behavior when they are installed in flexible base structures. In this study, a structure is subjected to a stationary random excitation and the root mean square of the controlled response was compared to an uncontrolled system to measure the TMD performance.…”
Section: Introductionmentioning
confidence: 99%